Bilateral Alternating Auditory Stimulations Facilitate Fear Extinction and Retrieval - Boukezzi, Sarah; Silva, Catarina; Nazarian, Bruno; Rousseau, Pierre-François; Guedj, Eric; Valenzuela-Moguillansky, Camila; Khalfa, Stéphanie (Frontiers in Psychology, 2017)
Disruption of fear conditioning, its extinction and its retrieval are at the core of Posttraumatic Stress Disorder (PTSD). Such deficits, especially fear extinction delay, disappear after Alternating Bilateral Stimulations (BLS) during Eye Movement Desensitization and Reprocessing (EMDR) therapy. An animal model of fear recovery, based on auditory cued fear conditioning and extinction learning, recently showed that BLS facilitate fear extinction and fear extinction retrieval. Our goal was to determine if these previous results found in animals can be reproduced in humans. Twenty-two healthy participants took part in a classical fear conditioning, extinction, and extinction recall paradigm. Behavioral responses (fear expectations) as well as psychophysiological measures (skin conductance responses [SCR]) were recorded. The results showed a significant fear expectation decrease during fear extinction with BLS. Additionally, SCR for fear extinction retrieval were significantly lower with BLS. Our results demonstrate the importance of BLS to reduce negative emotions, and provide a successful model to further explore the neural mechanisms underlying the sole BLS effect in the EMDR.